Systemic fates of non-classically restricted, commensal specific T cells - Farley, TK (2023)
Inflammatory Bowel Diseases (IBD), encompassing both Crohn’s disease and ulcerative colitis, are characterized by destruction of the gut epithelial barrier, dysbiosis and aberrant immune reactivity to the microbiota. Although multiple studies have revealed CD8+ T cell signatures in the tissues and circulating PBMC of patients with IBD, the role of CD8+ T cells in the initiation or perpetuation of disease has remained understudied.